Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening - Muslih Muslih; Nisa Zamara (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2022)
The purpose of this study was to determine the effect of discipline and work motivation on employee performance with satisfaction as an intervening variable at Bank Mandiri Medan City Hall area. Either directly or indirectly. This study uses a quantitative approach and statistical analysis, namely the partial least square - structural inquiry model (PLSSEM) which aims to perform path analysis with latent variables. This research was conducted at Bank Mandiri Medan Balaikota area, the sample in this study used slovin withdrawal which obtained 51 employees who became the research sample. The results showed that work discipline, work motivation and job satisfaction had a significant positive effect on employee performance. Work discipline and work motivation have a positive effect on employee performance. Indirectly, work discipline affects employee performance through job satisfaction, work motivation does not affect employee performance through job satisfaction.